Warming of Atlantic Water in two west Spitsbergen fjords over the last century (1912-2009) - Pavlov, Alexey K.; Tverberg, Vigdis; Ivanov, Boris; Nilsen, Frank; Falk-Petersen, Stig; Granskog, Mats A. (Polar Research, 2013)
The recently observed warming of west Spitsbergen fjords has led to anomalous sea-ice conditions and has implications for the marine ecosystem. We investigated long-term trends of maximum temperature of AtlanticWater (AW) in two west Spitsbergen fjords. The data set is composed of more than 400 oceanographic stations for Isfjorden and Grønfjorden (78.18N), spanning from 1876 to 2009. Trends throughout the last century (1912 2009) indicate an increase of 1.98C and 2.18C in the maximum temperature during autumn for Isfjorden and Grønfjorden, respectively. A recent warming event in the beginning of the 21st century is found to be more than 18C higher than the second warmest period in the time series. Mean sea-level pressure (MSLP) data from ERA-40 and ERA-Interim data sets produced by the European Centre for Medium-Range Weather Forecasts and mean temperature in the core of the West Spitsbergen Current (WSC) at the Sørkapp Section along 76.38N were used to explain the variability of the maximum temperature. A correlation analysis confirmed previous findings, showing that variability in the oceanography of the fjords can be explained mainly by two external factors: AW temperature variability in the WSC and regional patterns of the wind stress field. To take both processes into consideration, a multiple regression model accounting for temperature in the WSC core and MSLP over the area was developed. The predicted time series shows a reasonable agreement with observed maxima temperature in Isfjorden for the period 1977 2009 (N 24), with a statistically significant multiple correlation coefficient of 0.60 (R2 0.36) at PB0.05.